Darth Paper strikes back : an Origami Yoda book - Angleberger, Tom.; local (New York : Amulet Books, 2011)
After several Origami Yoda-related incidences, Dwight is suspended for being a troublemaker and Yoda asks Tommy and Kellen to save Dwight by creating a case fil
"Bonus game and origami instructions"--Cover p. [4].
e that proves Dwight is an asset to Ralph McQuarrie Middle School.
Follett Library Resources
Keywords: Follett Library Resources; sears -- Yoda (Fictitious character : Lucas); Juvenile fiction. -- Finger puppets; Juvenile fiction. -- Origami; Juvenile fiction. -- Eccentrics and eccentricities; Juvenile fiction. -- Interpersonal relations; Juvenile fiction. -- Middle schools; Juvenile fiction. -- Schools; Juvenile fiction. -- Yoda (Fictitious character : Lucas); Fiction. -- Finger puppets; Fiction. -- Origami; Fiction. -- Eccentrics and eccentricities; Fiction. -- Interpersonal relations; Fiction. -- Middle schools; Fiction. -- Schools; Fiction. -- Yoda (Fictional character : Lucas); sears -- Puppets and puppet plays; sears -- Origami; sears -- Eccentrics and eccentricities; sears -- Interpersonal relations; sears -- Middle schools; sears; sears